Velocity and wall shear stress of 18% EDTA irrigation solution flow in the removal of Ca(OH)2 with computational fluid dynamic analysis - Muryani, Anna; Dharsono, Hendra Dian Adhita; Zuleika, Zuleika; Moelyadi, Mochammad Agoes; Fatriadi, Fajar (Universitas Padjadjaran, 2019)
Introduction: Ethylene Diamine Tetra Acetic Acid (EDTA) 18% irrigation solution is one of the chelating agents that able to remove calcium hydroxide (Ca(OH)2) from the root canal wall. Failure of root canal treatment can be caused by the presence of residual calcium hydroxide in the root canal wall, thus blocking the bond between the medication and root canal filling material with the root canal wall. This study was aimed to observe the EDTA 18% flow in removing the Ca(OH)2 using CFD analysis. Methods: This research was descriptive. Cleanliness of the root canal wall from Ca(OH)2 medicament using EDTA 18% irrigation was analysed using the CFD method with test specimens in the form of resin blocks made according to the characteristics of the root canal. The irrigation needle used was side-vented with a position of 3 mm from the apical tooth. Stage analysis of root canal geometry was performed using Computational Fluid Dynamics (CFD) analysis to observe the characteristics of irrigation solutions in root canals in 3D. Results: The streamlined characteristics of EDTA 18% irrigation solution showed a unique behaviour due to the features of the side-vent shaped irrigation needle. Irrigation flow in the crown area of the inlet (side-vented irrigation needle) showed low velocity so that the fluid flow when exiting the inlet was more towards the apical than the outlet (root canal orifice). Conclusion: Velocity and wall shear stress of EDTA 18% showed the results validation conformity between experimental and CFD, that the maximum velocity of EDTA 18% is 19 ms-1 and EDTA 18% wall shear stress is 1.56 KPa for calcium hydroxide removal observed from the CFD study. Keywords: Computational fluid dynamics, EDTA 18%, calcium hydroxide (Ca(OH)2), velocity, wall shear stress